James Stuart and "the establishment of a living source of tradition' - Hamilton, Carolyn (My University, 1994)
In the late 1970s and the 1980s scholarship on the Zulu kingdom under Shaka changed significantly as scholars began for the first time to draw heavily on recorded African oral tradition as an historical source, and to use local and regional histories as counterweights to official accounts emanating from royal houses and associated senior royal clans.(1) The major source of such oral traditions pertinent to the area including and adjacent to the Zulu kingdom is the papers of the Natal colonial official, James Stuart (1868-1942)
African Studies Seminar series. Paper presented 1 August, 1994
Keywords: Stuart, James, 1868-1942; Oral tradition. South Africa. KwaZulu-Natal. Research; Zulu (African people). Historiography